Transient Stability Improvement Using UPFC-SMES in A Multi Machine Power System - Kantilal Dayalal Joshi; Vinod Chandrakar (International Journal of Applied Power Engineering (IJAPE), 2016)
Unified Power Flow Controller (UPFC) is a Voltage sourced converter based Flexible A.C.Transmission  (FACTS) controller which has a capability of simultaneously or selectively controlling all the parameters affecting transmission of power.  With emphasis on harnessing renewable energy many energy storage technologies are being used. Superconducting magnetic energy storage (SMES) stores energy in magnetic form by means of a D.C. current circulating in a superconducting coil. To exchange power with SMES a power electronic interface is required. Feasibility of interfacing SMES to D.C. link of UPFC has been explored in this paper. A multimachine system with a long transmission line is compensated by UPFC-SMES .A DC-DC chopper modulates power of SMES so as to improve the transient stability of system. Complete simulation has been done using MATLAB/Simulink which shows improvement of first peak, damping of oscillations & improvement in critical clearing time.